A reader response method not just for 'you'. (August 2019) - Bell, Alice; Ensslin, Astrid; van der Bom, Isabelle; Smith, Jen
This article contributes to empirical literary studies by offering a new reader response method for examining targeted textual features. With the aim of further establishing the new paradigm of reader response research in stylistics, we utilise a Likert scale – a tool that is usually used to generate data that is analysed quantitatively – to elicit qualitative data and, crucially, show how that data can be synthesised with an analysis of the primary text to provide empirically based conclusions relevant to particular textual features for cognitive narratology and stylistics. While we offer a new method that can be used to investigate textual features in all kinds of text, we exemplify our approach via the investigation of second-person narration in geniwate and Larsen's digital fiction The Princess Murderer and provide a new understanding of the experiential nature of ambiguous forms of 'you' in fiction. Our stylistic analyses show how responses can be generated by linguistic features in the text. We then analyse reader responses to those examples and show that this can provide a more nuanced account of 'you' narratives than a stylistic analysis alone because it affords insight into how different readers do or do not psychologically project into and/or assume the role of 'you'. Our results represent the first time that current typologies of the second person have been empirically tested and we are the first study to find an empirical basis for doubly deictic 'you'. We therefore contribute a new empirically based understanding of how readers experience ambiguous forms of 'you' in fiction.